Impact of Dispensing Services in an Independent Community Pharmacy - Kaleb Payne; Elizabeth J. Unni; Benjamin Jolley (MDPI AG, 2019)
With approximately 300 prescriptions dispensed per day in a typical community pharmacy, several activities take place to ensure the safe dispensing of medicines. While some of these activities are common for all prescriptions, others need further activities such as prescription clarification. These activities are important to avoid any potential harm to the patient and improve medication adherence. The objective of this study was to measure the impact of these additional dispensing services in a community pharmacy by evaluating the documented patient notes. Two-hundred patients with annotations on their profiles between 1 July and 31 August 2018 were randomly selected and 322 notes were analyzed. The average number of notes per patient was 1.6. The majority of the notes were about contacting the patient/caregiver for prescription clarification (86.8%). When analyzed based on Medication Therapy Problems, 54.7% were related to adherence and 35.4% to safety. Using the cost saving estimate from the literature for each averted adverse event, these activities resulted in a minimum cost saving of $10,458. This study was able to show the positive impacts that everyday dispensing services in an independent community pharmacy have on ensuring the safe use of medication, thus potentially preventing adverse drug events and reducing health care costs.